The role proximity plays in university-driven social networks. The case of the US and EU life-science clusters - Małgorzata Runiewicz-Wardyn (Journal of Entrepreneurship, Management and Innovation)
Over the last decade, the research in the field of technology and innovation has progressed towards the development of the notion of an ‘ecosystem’ that lays within the idea that innovation and technological advances stem from collective research efforts and social interactions. The paper delivers new insights on successful university-based innovation ecosystems, by exploring the role of proximities in university-driven social networks. Two research problems are discussed: 1/ the structure and dynamics of university-driven social networks, and 2/ the role of proximities as pre-conditions for stronger social ties and more frequent interactions. The author applies a qualitative interview and direct observation methods on the example of several selected life-science university-based ecosystems in the EU and the US. The study identifies several fundamental relationships: (1) the presence of high physical, cognitive and organizational proximities within university-based ecosystems contributes to social networking and the interchange of knowledge; (2) cognitive and organizational proximities are the primary motives for social collaborations within university-based ecosystems; (3) physical proximity matters most when strong social networks already exist; (4) physical proximity allows ecosystem players to have more informal interactions; (5) cultural and social proximities increase more effective communication, trust and knowledge sharing; (6) social networking within university-based ecosystems may be partially engineered by the brokerage function of intermediary organizations and managers, aiming to narrow organizational, technological and cognitive proximities between ecosystem players. Bridging organizational, cognitive and social distances must be one of the regional innovation policies priorities. Further research must consider increasing technological convergence, shortening technological cycles and globalization processes within the life-science sector.